Tin/polypyrrole composite anode using sodium carboxymethyl cellulose binder for lithium-ion batteries - Chou, Shu-Lei; Gao, Xuan-Wen; Wang, Jia-Zhao; Wexler, David; Wang, Zhao-Xiang; Chen, Li-Quan; Liu, Hua-Kun (Dalton transactions : an international journal of inorganic chemistry, 2011)
A tin nanoparticle/polypyrrole (nano-Sn/PPy) composite was prepared by chemically reducing and coating Sn nanoparticles onto the PPy surface. The composite shows a much higher surface area than the pure nano-Sn reference sample, due to the porous higher surface area of PPy and the much smaller size of Sn in the nano-Sn/PPy composite than in the pure tin nanoparticle sample. Poly(vinylidene fluoride) (PVDF) and sodium carboxymethyl cellulose (CMC) were also used as binders, and the electrochemical performance was investigated. The electrochemical results show that both the capacity retention and the rate capability are in the same order of nano-Sn/PPy-CMC > nano-Sn/PPy-PVDF > nano-Sn-CMC > nano-Sn-PVDF. Scanning electronic microscopy (SEM) and electrochemical impedance spectroscopy (EIS) results show that CMC can prevent the formation of cracks in electrodes caused by the big volume changes during the charge-discharge process, and the PPy in the composite can provide a conducting matrix and alleviate the agglomeration of Sn nanoparticles. The present results indicate that the nano-Sn/PPy composite could be suitable for the next generation of anode materials with relatively good capacity retention and rate capability. A nano-Sn/PPy composite as an anode using sodium carboxymethyl cellulose as a binder for a lithium-ion battery shows improved capacity retention and rate capability.